3-D GPR visualization technique integrated with electric resistivity tomography for characterizing near-surface fractures and cavities in limestone. Issue 1 (31st December 2022) - Gaballah, Mahmoud; Alharbi, Thamer
Abstract : Near-surface geophysical techniques, (i.e. ground-penetrating radar (GPR) and electric resistivity tomography (ERT)), continue to enable great possibilities for 3-D visualization of fractures and cavities. An integrated survey, including GPR and ERT, was used for mapping and evaluating a complex subsurface fracture network in Eocene limestone at Al-Mokattam site, Egypt. While only GPR was available to investigate an engineering site of about 200 × 300 m, located in Riyadh city, Saudi Arabia, for cavity detection. At the Egyptian site, GPR data were acquired with a GSSI SIR2000 system using a 400 MHz shielded antenna with 0.2 m in-line spacing. GPR data visualized using an isosurface rendering combined with inverted ERT allowed us to identify and follow the fracture system, which was mainly filled with low-resistivity sediment; such fractured limestone may cause landslides. GPR data at the Riyadh site were acquired using the RAMAC system with a 100 MHz shielded antenna attached to a GPS with real-time kinematic total station equipment; GPR data confirmed the possible presence of cavities at different depths, which may cause severe damage during building construction. In this paper, we demonstrated the efficiency of each geophysical technique available for solving subsurface engineering problems, leading to future improvements in site safety. Additionally, we indicated the efficiency of an advanced 3-D GPR visualization technique (isosurface rendering) for improving fracture and cavity detection, characterization and interpretation.